Determinants of agricultural credit acquisition for the Land Bank of South Africa : case study of smallholder farmers in peri-urban areas of Mopani District, Limpopo Province, South Africa - Braide, Tamunotonye Mayowa (University of Limpopo, 2015)
Capital is one of the most important factors of production. In South Africa, among other things, lack of finance is one of the fundamental problems hampering production, productivity and income of rural farm households. Smallholder farmers in South Africa face many challenges in accessing financial services, despite the numerous reforms undertaken by the government to transform smallholder agriculture and improve its contribution to rural income, food security and employment. Many rural farmers have remained in poverty with limited capacity to access means of production like credit to militate against hunger and poverty. The aim of the study was to analyse the determinants of loan acquisition from the Land Bank of South Africa by smallholder farmers in peri-urban areas of Mopani District in Limpopo province. The objectives were to identify the constraints smallholder farmers face in accessing credit, to analyse the determinants of loan acquisition among smallholder farmers and to profile loan acquisitions of the farmers based on their socio-economic characteristics. The study used primary data, which was collected through a field survey. The method that was used to collect information was face-to-face interviews using structured questionnaires. The study employed the snowball sampling technique in its data collection strategy due to the fact that the population size was unknown due to the sensitivity of the study. Smallholder farmers were classified as beneficiaries and non-beneficiaries of the Land Bank. The total sample size comprised 62 smallholder farmers from the peri-urban areas of Tzaneen and Giyani of Mopani District, Limpopo province. The data was captured into the Statistical Package for Social Sciences (SPSS). Principal component analysis was carried out so as to get the principal factors or new uncorrelated variables that affect the ability of smallholder farmers to access credit from the Land bank and it was also use to profile the farmers according to the socio-economic variables. After carrying out the principal component analysis, probit analysis was then used to determine the relationship between the socio-economic characteristics of smallholder farmers and their ability to access credit. The principal component analysis (PCA) extracted important information from the data table and expressed the information as a set of new orthogonal variables called principal components. The PCA reduced the original variables to six (6) principal components. The six (6) principal components were labelled as; component 1 (Old-experience smallholder farmers), component 2 (business-oriented smallholder farmers), component 3 (part-time smallholder farmers), component 4 (smallholder farmers who receive grants based on gender), component 5 (smallholder farmers with fixed assets and their distance to the nearest town) and component 6 (smallholder farmers who belong to cooperatives). The smallholder farmers where classified and ranked into this six components based on their level of accessibility to agricultural credit from the Land Bank. A majority of the smallholder farmers involved in the study were ranked lowly on their level of accessibility to agricultural credit from the Land Bank; they were classified under the old and experienced smallholder farmers. Probit regression result indicated that the variables gender, education, farm income, pension, land size, cooperative, fixed assets and registered business had a significant positive influence on smallholder farmers’ accessing agricultural credit from the Land Bank in the last three years. In addition, marital status, farming experience, off-farm income, loose assets, farm commodity and farm record had an insignificant positive influence. The probit result also showed that the variables age had a significant negative influence on smallholder farmers’ accessing agricultural credit. In addition, household size, employment, distance to the nearest town and farmers’ association had an insignificant negative influence. Based on the results of the study, it is recommended that the government and other institutions could design agricultural credit programmes that are promptly responsive to the needs of the smallholdCapital is one of the most important factors of production. In South Africa, among other things, lack of finance is one of the fundamental problems hampering production, productivity and income of rural farm households. Smallholder farmers in South Africa face many challenges in accessing financial services, despite the numerous reforms undertaken by the government to transform smallholder agriculture and improve its contribution to rural income, food security and employment. Many rural farmers have remained in poverty with limited capacity to access means of production like credit to militate against hunger and poverty. The aim of the study was to analyse the determinants of loan acquisition from the Land Bank of South Africa by smallholder farmers in peri-urban areas of Mopani District in Limpopo province. The objectives were to identify the constraints smallholder farmers face in accessing credit, to analyse the determinants of loan acquisition among smallholder farmers and to profile loan acquisitions of the farmers based on their socio-economic characteristics. The study used primary data, which was collected through a field survey. The method that was used to collect information was face-to-face interviews using structured questionnaires. The study employed the snowball sampling technique in its data collection strategy due to the fact that the population size was unknown due to the sensitivity of the study. Smallholder farmers were classified as beneficiaries and non-beneficiaries of the Land Bank. The total sample size comprised 62 smallholder farmers from the peri-urban areas of Tzaneen and Giyani of Mopani District, Limpopo province. The data was captured into the Statistical Package for Social Sciences (SPSS). Principal component analysis was carried out so as to get the principal factors or new uncorrelated variables that affect the ability of smallholder farmers to access credit from the Land bank and it was also use to profile the farmers according to the socio-economic variables. After carrying out the principal component analysis, probit analysis was then used to determine the relationship between the socio-economic characteristics of smallholder farmers and their ability to access credit. ii The principal component analysis (PCA) extracted important information from the data table and expressed the information as a set of new orthogonal variables called principal components. The PCA reduced the original variables to six (6) principal components. The six (6) principal components were labelled as; component 1 (Old-experience smallholder farmers), component 2 (business-oriented smallholder farmers), component 3 (part-time smallholder farmers), component 4 (smallholder farmers who receive grants based on gender), component 5 (smallholder farmers with fixed assets and their distance to the nearest town) and component 6 (smallholder farmers who belong to cooperatives). The smallholder farmers where classified and ranked into this six components based on their level of accessibility to agricultural credit from the Land Bank. A majority of the smallholder farmers involved in the study were ranked lowly on their level of accessibility to agricultural credit from the Land Bank; they were classified under the old and experienced smallholder farmers. Probit regression result indicated that the variables gender, education, farm income, pension, land size, cooperative, fixed assets and registered business had a significant positive influence on smallholder farmers’ accessing agricultural credit from the Land Bank in the last three years. In addition, marital status, farming experience, off-farm income, loose assets, farm commodity and farm record had an insignificant positive influence. The probit result also showed that the variables age had a significant negative influence on smallholder farmers’ accessing agricultural credit. In addition, household size, employment, distance to the nearest town and farmers’ association had an insignificant negative influence. Based on the results of the study, it is recommended that the government and other institutions could design agricultural credit programmes that are promptly responsive to the needs of the smallholder farmers. It was also recommended that the Department of Agriculture, Forestry and Fisheries (DAFF) should ensure that the agricultural extension officers are well equipped to be able to disseminate their information to farmers irrespective of their location
Thesis (M.Sc.(Agricultural Economics)) -- University of Limpopo, 2015
Keywords: Capital; Factors of production; South Africa; Finance; Smallholder farmers; Agricultural credit -- South Africa